Evaluation of Sintering Behavior of Premix Al-Zn-Mg-Cu Alloy Powder - Haris Rudianto; Gwang Joo Jang; Sang Sun Yang; Yong Jin Kim; Ivo Dlouhy (Advances in Materials Science and Engineering)
Sintering of light aluminium alloys powder has been investigated as a way to substitute steels in automotive and aerospace industries. Premix Al-5.5Zn-2.5Mg-0.5Cu composite powder called Alumix 431D was analyzed in this research. Sintering was carried out under ultra high purity nitrogen gas and before reaching sintering temperature, green samples were delubricated at 400°C for 30 min. The powder possesses high sinterability by reaching 96% relative density at 580°C sintering temperature. Formation of liquid phase seems to support achieving high sintering density. Optimum mechanical properties also were obtained under those conditions. T6 heat treatment was done to improve the mechanical properties by formation of precipitation strengthening, and MgZn2 appears to be dominant strengthening precipitate. X-ray diffraction, optical microscopy, and SEM-EDS were used to characterize powder, and sintered and heat treated samples.